1990
DOI: 10.1136/ard.49.11.906
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity and joint damage progression in early rheumatoid arthritis: relation to IgG, IgA, and IgM rheumatoid factor.

Abstract: The clinical and biochemical correlations with joint damage progression over two years in a consecutive group of 68 patients with rheumatoid arthritis with disease duration of less than two years are reported. Joint damage was assessed with Larsen's severity scale and a measure of change in progression rate constructed. Initial haemoglobin concentration, Ritchie index, and Waaler-Rose titre in combination accounted for one third of the variance in joint damage progression. Rheumatoid factor (RF) Patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 16 publications
(3 reference statements)
4
25
0
1
Order By: Relevance
“…It is generally accepted that rheumatoid factorpositive patients have worse outcomes with respect to radiologic progression, disease activity, and functional ability (24,25). Our results suggest that the presence of rheumatoid factor determines whether fluctuations in joint inflammation lead to important radiologic damage.…”
Section: Discussionsupporting
confidence: 54%
“…It is generally accepted that rheumatoid factorpositive patients have worse outcomes with respect to radiologic progression, disease activity, and functional ability (24,25). Our results suggest that the presence of rheumatoid factor determines whether fluctuations in joint inflammation lead to important radiologic damage.…”
Section: Discussionsupporting
confidence: 54%
“…Our results at the 2-year followup are comparable with those of Eberhardt et a1 (33)(34)(35)(36), in which 89-113 Swedish patients with early RA were enrolled and followed up using the same methods as in our study, and actually simultaneously with the time of enrollment in our study. The proportions of patients with R F seropositivity, erosive disease, and HLA-DR4 and the degree of disease activity (Mallya score) at entry were similar in the 2 studies, while the median values of the Larsen index and MHAQ score at enrollment were higher in the Swedish study than in ours.…”
Section: Discussionsupporting
confidence: 90%
“…We considered the studies by Eberhardt et a1 (33)(34)(35)(36), performed in Sweden, to be most compatible with ours because the patients were enrolled simultaneously and disease activity and outcome were assessed by the same methods. Baseline demographic and clinical characteristics of the patients in the present study and the Swedish cohort are described in Table 7.…”
Section: Mottonen Et Almentioning
confidence: 98%
See 1 more Smart Citation
“…We have earlier reported that IgG RF showed the strongest relation to joint damage after two years of follow up in this cohort. 47 The discrepant findings might be explained by the shorter follow up period, different assessment methods, and fewer patients.…”
Section: Discussionmentioning
confidence: 99%